PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN LCD BERBASIS POWER POINT TERHADAP HASIL BELAJAR SOSIOLOGI SISWA KELAS XI IIS 2 SMA MUHAMMADIYAH 1 PONTIANAK - Retno Yuli Setyowati; Yohanes Bahari; Amrazi Zakso (Universitas Tanjungpura, 2019)
AbstractThe influence of the sejauhmana LCD-based learning media use power point against the results of the study of Sociology class XI IIS 2 SMA Muhammadiyah 1 Pontianak This can be indicated with (1) the use of power point-based learning media is more effective and efficient way to improve student learning outcomes, i.e. obtained average value of experimental class was 82.03 comparison of average value class control i.e. of 70.80. (2) Student Learning Outcomes by using LCD-based learning media power point more to contribute good learning results achievement compared to conventional learning media. This can be shown by the number of students who scored many as 16 students (53.33%) LCD-based learning with media power point, as opposed to 3 students (9.99%) the thoroughly with LCD-based learning using media power point more contributes to the achievement of a good learning results compared to conventional learning media. Keywords: LCD-based Power Poin, Results of the study, and The Media.